James House BEST Proactive Parenting Programme: experiences of South African parents - Kader, Zainab; Roman, Nicolette V (Argumentum, 2019)
The parent-child relationship often becomes challenging during the period of adolescence and it is community-based organisations, which take on the role of educating parents to improve the parent-adolescent relationship. The contribution of these interventions or programmes is not documented in South Africa. The James House BEST Proactive Parenting Programme prepares parents to manage the challenging behaviours of their adolescents. This was a qualitative study exploring the experiences of 24 parents living in at-risk resource-constrained communities who had attended the training workshops. Four themes emerged from the data (a) experiences of attending the proactive parenting workshops; (b) meaning of being a parent; (c) approaches to parenting and (d) the role of the father. In general, parents had a very positive experience and found that their relationships with their adolescents had improved. In particular, the results suggest that children require parental support, guidance, and parental involvement.